The peepshow: the murders at Rillington Place - Summerscale, Kate (Penguin Press, 2024)
"From the Edgar Award-winning author of The Haunting of Alma Fielding, the tale of two journalists competing to solve the notorious Christie murders in postwar London In March 1953, London police discovered the bodies of three young women hidden in a wall at 10 Rillington Place, a dingy rowhouse in Notting Hill. On searching the building, they found another body beneath the floorboards, then an array of human bones in the garden. They launched a nationwide manhunt for the tenant of the ground-floor apartment, a softly spoken former policeman named Reg Christie. But they had already investigated a double murder at 10 Rillington Place three years before, and the killer was hanged. Did they get the wrong man? The story was an instant sensation. The star reporter Harry Procter chased after the scoop on Christie. The eminent crime writer Fryn Tennyson Jesse begged her editor to let her cover the case. To Harry and Fryn, Christie seemed a new kind of murderer: he was vacant, impersonal, a creature of a brutish postwar world. Christie liked to watch women, they discovered, and he liked to kill them. They realized that he might also have engineered a terrible miscarriage of justice. In this riveting true story, Kate Summerscale mines the archives to uncover the lives of Christie's victims, the tabloid frenzy that their deaths inspired, and the truth about what happened inside the house. What she finds sheds fascinating light on the origins of our fixation with true crime-and suggests a new solution to one of the most notorious cases of the century"-- Provided by publisher